Case reportCheilitis – case study and literature review - Rosińska-Więckowicz, Anna; Misterska, Małgorzata; Bartoszak, Leszek; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Inflammatory lesions of the lips are usually a cosmetic complaint, but may also be a relevant manifestation of systemic diseases. Cheilitis and angular cheilitis are usually considered as distinct entities as there are different underlying causes of the two conditions. However, they may also coexist with each other. Cheilitis may also coexist with or precede the onset of numerous systemic disorders. We present a patient with an 8-year history of cheilitis. Moreover, different possible underlying causes in the differential diagnosis and treatment possibilities are presented.